Subacute right ventricle perforation: a pacemaker lead complication. Issue 5 (12th May 2021) - Allouche, Emna; Chargui, Soumaya; Fathi, Marwa; Bezdah, Leila
Abstract : Myocardial perforation is an uncommon but potentially life-threatening complication of pacemaker and implantable cardioverter-defibrillator. Myocardial perforation may be acute, subacute or chronic when it occurs within 24 hours of the device insertion; between 1 day and 30 days; and more than 30 days after implantation. This complication may occur in 1.7%–7% of patients. However, subacute myocardial perforation is rare and affects 0.5%–1.2% of patients. We report the case of an 85-year-old patient with a pacemaker failure 10 days after implantation due to a subacute myocardial perforation caused by an active fixation ventricular lead. Transthoracic echocardiography showed penetration of the ventricular lead through the right ventricular apex into the pericardium without any pericardial effusion. We confirmed myocardial perforation by a CT scan. We referred her to the surgery ward where she was successfully managed.